Effectiveness of Using Blended Learning Media in Christian Religious Education - Bonar Dominggos Simanjuntak; Resiani Simamora; Daniel Ricel Fredik Polii; Darmin Usman Zega (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study is to describe the effectiveness of using blended learning through Christian Religious Education. Blended learning is a solution to society's high need for education but is hindered by busyness, time and distance, as well as answering the wishes of some people who still want face-to-face learning. Christian religious education also applies blended learning to free individuals from the shackles of ignorance. Therefore, this research has a background problem, whether blended learning is effectively used in Christian religious education. The method used in this research is a descriptive qualitative method approach. The research process was carried out using library study techniques, namely collecting data, sorting, reading, analyzing and drawing conclusions. This research will produce a description of blended learning effectively used in Christian Religious Education.